2022
DOI: 10.1007/s00784-022-04790-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temporary cements and their removal methods on the bond strength of indirect restoration: a systematic review and meta-analysis

Abstract: Objectives For a conventional indirect restoration, temporary cementation inevitably contaminated collapsed dentin collagen. The purpose of this review was to evaluate the optimal strategy for minimizing its negative effects. Material and methods Databases such as PubMed, Web of Science, EMBASE, and the Cochrane Library were searched for in vitro studies, involving the influence of immediate dentin sealing (IDS), different temporary cements, and their remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…This method was considered less aggressive than the other methods, but it could be responsible for the lower SBS in the protocols involving immediate dentin sealing and bonding after 2 weeks with provisional restoration and immediate dentin sealing with flowable resin composite reinforcement and bonding after 2 weeks with provisional restoration than in the immediate sealing with immediate bonding group; remnants of provisional restoration material might persist on the surface and interfere with the adhesion of resin cement [2]. In addition, Ding et al [48] concluded that the pumice and hand instrument removal methods were ineffective and unreliable for adequate cleaning. Their justification was that some dentinal tubules may be occluded by particle remnants due to the force of rotation, which would reduce wettability and roughness [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method was considered less aggressive than the other methods, but it could be responsible for the lower SBS in the protocols involving immediate dentin sealing and bonding after 2 weeks with provisional restoration and immediate dentin sealing with flowable resin composite reinforcement and bonding after 2 weeks with provisional restoration than in the immediate sealing with immediate bonding group; remnants of provisional restoration material might persist on the surface and interfere with the adhesion of resin cement [2]. In addition, Ding et al [48] concluded that the pumice and hand instrument removal methods were ineffective and unreliable for adequate cleaning. Their justification was that some dentinal tubules may be occluded by particle remnants due to the force of rotation, which would reduce wettability and roughness [48].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ding et al [48] concluded that the pumice and hand instrument removal methods were ineffective and unreliable for adequate cleaning. Their justification was that some dentinal tubules may be occluded by particle remnants due to the force of rotation, which would reduce wettability and roughness [48]. Hence, using a dental loupe to explore the dental surfaces before luting the definitive restoration is advised.…”
Section: Discussionmentioning
confidence: 99%
“…However, when bonding was needed, two cements could be chosen according to different preparation designs of veneers. Zinc polycarboxylate cement is pulp-friendly and easy to clean [ 35 ], which could be used for temporary bonding of veneers with incisal overlap preparation. For the veneers prepared by window, feather or bevel, they were cemented with a point adhesion technique due to the poor retention [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…De laatste jaren is er veel onderzoek gedaan naar IDS. Alleen al in 2022 verschenen 3 systematische literatuuronderzoeken met meta-analyses over dit onderwerp (Ding et al, 2022;Hardan et al, 2022;Josic et al, 2022). Tijdens de IDS-procedure wordt het adhesief direct na preparatie van het dentine aangebracht (vóór het afdrukken), zie casus (afb.…”
Section: Antwoord Uit De Literatuurunclassified
“…Deze toename van hechtsterkte wordt verkregen omdat het dentine niet kan worden gecontamineerd met een tijdelijk cement of tijdelijke restauratie. In een zeer recent literatuuronderzoek en meta-analyse werd het voordeel (significant betere hechtsterkte) van een IDS en het voorkomen van contaminatie benadrukt (Ding et al, 2022;Hardan et al, 2022). Het andere systematische literatuuronderzoek is wat minder positief omdat dit vooral over postoperatieve pijn rapporteerde (Josic et al, 2022).…”
Section: Antwoord Uit De Literatuurunclassified